PHARMACOLOGICAL EVALUATION OF THE INHIBITORY EFFECT OF EXTRACTS FROM ANCHIETIA-SALUTARIS ON THE HISTAMINE-RELEASE INDUCED IN THE RAT AND THE GUINEA-PIG - Gomes, J. C.; Distasi, L. C.; Sgarbosa, F.; Barata, LES (Karger, 1994)
The tea made with leaves and stems of plant Anchietia salutaris is traditionally used in Brazil to treat allergies. We examined the effects of a crude aqueous extract and of purified fractions of this plant on the histamine release induced in rat and guinea pig tissues. The crude extract (3-10 mu g/ml) inhibits the histamine release induced by compound 48/80 (0.5 mu g/ml) and antigen in rat peritoneal mast cells. The inhibition is significant after 10 s of preincubation and is completed after 3 min. The crude extract dissolved in the perfusion fluid (1-30 mu g/ml) also inhibits the histamine release induced in guinea pig heart by cardiac anaphylaxis and in hearts from pretreated animals (10-100 mg/kg i.p.). In pretreated animals, the effect manifests after 3 h, is maximum after 12 h and disappears after 48 h. The histamine release induced in isolated guinea pig heart by ionophore A23187 is inhibited by similar doses as in antigen-induced histamine release. Extraction with solvents concentrated the active principle (s) in the hexane fractions, as demonstrated by the inhibition of the histamine release induced by antigen in isolated cells from guinea pig heart dispersed with collagenase. In subfractions produced by the fractionation of the hexane fraction, the active principle(s) concentrated in the subfractions obtained by extraction with hexane and ethyl acetate, which shows the low polarity of the compound(s). The same subfractions that inhibit the histamine release induced by antigen in cells from guinea pig heart also inhibit pulmonary cells. Our result show that A. salutaris contains low-polarity compound(s) that inhibit the histamine release induced by three different mechanisms in mast cells from two animal species. These facts suggest that the active principle(s) of A, salutaris could be useful in the treatment of allergies and/or as a tool for the study of mast cell secretions.
Keywords: HISTAMINE RELEASE; ANCHIETIA SALUTARIS; GUINEA PIGS MAST CELLS; RAT MAST CELLS